KARAKTERISTIK ORGANIOLEPTIK OTAK-OTAK IKAN YANG DIBERI EDIBLE COATING KARAGINAN DENGAN PENAMBAHAN ASAP CAIR - Bariah, Eka Irma Q; Berhimpon, Siegfried; Mongi, Eunike Louisje (Sam Ratulangi University, 2015)
Edible coating is a new type of packaging made of biopolymer. The advantages of edible coating is enable to protect the food product, the original appearance of the product can be maintained and the product can be eaten as well as environmentally friendly. The study aim was to look at the organoleptic characteristics of fish cake coated with edible coating of carrageenan were given a liquid smoke. The treatmentsÂ given were variation of carrageenan concentration i,e. 0%, 1%, 1,5%, 2%, 2,5%, 3%. The experiment was designed using a Completely Randomized Design (CRD). To determine the effect of treatments, the data were tested using organoleptical tests consists of hedonic and texture.The results shown that hedonic test of the appearance and color of the raw sample have significant effect (p>0,05), while the other test showed no significant effect (p>0,05). However, the organoleptical score for taste, smell and texture shown a tendency that the fish cake coated, haveÂ higher score than without coated.Â Keywords: Edible coating, Carrageenan, Fish cake, Liquid smoke.